Historical aspect as a fundamental importance apitherapy, time and place of this integrative healing methods in traditional medicine - Đorđević Nataša (Sestrinska reč, 2016)
The concept of apitherapy is relatively recent. However, honey, beeswax, propolis and other bee products are used in the human diet since the dawn of time. Contemporary, integrative approach to medicine, bee products now classified not only as-feeding, but also as products that affect healing and improvement of human health. Apitherapy, as a modern, integrative method in the function of human health, occupies an increasingly important place in the framework of the method of traditional medicine. Also it plays a significant role in the modern approach for the health of the human population.